A New Zn(II) Coordination Polymer Constructed by Flexible Carboxylate and Rigid Imidazole-Containing Coligands With a 2D+2D→3D Polycatenated Structure. Issue 9 (1st September 2016) - Feng, Xiuling; Chen, Wanping; Xiang, Bolin
Abstract : A new Zn (II) coordination polymer with benzophenone-4, 4′-dicarboxylic acid (H2 bpdc) and 1, 4-bis(imidazol-1-yl)benzene (bib) has been prepared by hydrothermal synthesis and characterized by single-crystal X-ray diffraction, IR, and EA. Complex, [Zn(bpdc) (bib)]·2H2 On (1 ), is triclinic, space group P -1 with a = 8.958(5), b = 11.336(5), c = 14.150(5) Å, α = 111.109(5), β = 95.077 (5)° γ = 98.504(5), V = 1310.0 (10) Å 3, Z = 2, Mr = 579.86, Dc = 1.470 g/cm 3, F (000) = 596, and µ = 0.991 mm −1 . The final refinement gave R = 0.0352 and wR = 0.0964 for 5191 reflections with I > 2σ( I ). X-ray diffraction analysis reveals that the complex1 displays a 2D+2D→3D polycatenated structure.